Monograph review Fesenko G. G. "Morphology of urban landscapes: cultural-philosophical interpretations" - K. I. Karpenko, (Ukrainian Cultural Studies, 2018)
The city as a factor of socio-political and cultural life has recently attracted more and more attention of researchers - the mass of diverse literature (art history, cultural studies, sociology, politics, urbanism) dedicated to this issue is constantly growing. However, there are few thorough and original cultural-philosophical works in the domestic philosophical and scientific literature. In our opinion, the monograph of H. G. Fesenko partially fills this lacuna. The author has a good understanding of the objectively complex philosophical and historical-cultural issues, and has also found her own way of understanding them.